Antifungal Activity of New Eugenol-Benzoxazole Hybrids against Candida spp. - Larissa Incerti Santos de Carvalho; Dalila Junqueira Alvarenga; Letícia Cruz Ferreira do Carmo; Lucas Gomes de Oliveira; Naiara Chaves Silva; Amanda Latércia Tranches Dias; Luiz Felipe Leomil Coelho; Thiago Belarmino de Souza; Danielle Ferreira Dias; Diogo Teixeira Carvalho (Journal of Chemistry)
Eugenol is a natural allylphenol responsible for a wide range of biological activities, especially antimicrobial. Benzoxazoles are heterocycles with recognized antimicrobial activities. This paper describes the design, synthesis, and the biological results for benzoxazole type derivatives of eugenol as antifungal agents. The products were obtained in good yields by a four-step synthetic sequence involving aromatic nitration, nitroreduction, amide formation, and cycle condensation. They were evaluated against species of Candida spp. in microdilution assays, and four products (5a, 5b′, 5c, and 5d′) were about five times more active than eugenol against C. albicans and C. glabrata. Two of them (5b′ and 5d′) showed good activity against C. krusei, a species which is naturally resistant to fluconazole. Furthermore, the active products were more selective than eugenol against human blood cells, showing that they are interesting substances for further optimization.